Ins and Outs of Heat Shock Proteins in Colorectal Carcinoma: Its Role in Carcinogenesis and Therapeutic Perspectives - Batoul Abi Zamer (MDPI AG, 2021)
Cancer cells can reprogram their metabolic activities and undergo uncontrolled proliferation by utilizing the power of heat shock proteins (HSPs). HSPs are highly conserved chaperones that facilitate the folding of intracellular proteins under stress. Constitutively, HSPs are expressed at low levels, but their expression upregulates in response to a wide variety of insults, including anticancer drugs, allowing cancer cells to develop chemoresistance. In recent years, several researchers have reported that HSPs could be an important therapeutic target in difficult-to-treat cancers such as colorectal carcinoma (CRC). Worldwide, CRC is the second most common type of cancer and the second leading cause of cancer-related deaths. The molecular complexity of CRC and the coexisting inflammatory conditions present a significant obstacle to developing effective treatment. Recently, considerable progress has been made in enhancing our understanding of the role of HSPs in CRC pathogenesis. Moreover, novel therapeutic strategies targeting HSPs, either alone or in combination with other anticancer agents, have been reported. Herein, we present an overview of the functional mechanisms and the diagnostic and prognostic potential of HSPs in CRC. We also discuss emerging anti-CRC strategies based on targeting HSPs.